The Influence Of Lifestyle And Financial Literacy On The Consumptive Behavior Of UNPAB Students - Triska Devi Ginting; Cahyo Pramono; Maya Macia Sari (Universitas Dehasen Bengkulu, 2026)
The rapid development of digitalization and the increasing use of e-commerce platforms have influenced students’ consumption patterns, leading to more consumptive behavior. This study aims to analyze the effect of lifestyle and financial literacy on online shopping consumptive behavior among Fintech Management students at Universitas Pembangunan Panca Budi (UNPAB). A quantitative approach was applied using a survey method through questionnaires distributed to 71 respondents selected through saturated sampling. Data analysis was conducted using SPSS software, including data quality tests, classical assumption tests, and multiple linear regression analysis. The results indicate that lifestyle has a positive and significant effect on consumptive behavior, while financial literacy has a negative but statistically insignificant effect. Simultaneously, lifestyle and financial literacy significantly influence consumptive behavior with a coefficient of determination of 0.667, indicating that 66.7% of the variation in consumptive behavior can be explained by the model. These findings suggest that lifestyle plays a more dominant role than financial literacy in shaping students’ consumption behavior in the digital era, highlighting the need for more practical financial literacy education.